Coordinative capacity (rhythm) through colombian folk dance in people with down syndrome (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2023)
Introduction: Colombian folk dance contributes to the development of harmonic movement patterns and potentiates the rhythm in those who practice it, but the real problem of the practice without knowledge of the dance base, which leads to hinder the ideal development of the capacities coordination, specifically of the rhythm and if you work in a population with Down Syndrome, it increases the problem, because it can generate a decrease in the quality of life of this population. Objective: The present study aimed to determine the effect of a Colombian folk dance program on the coordination capacity, specifically the rhythm of people with Down syndrome from the Champions of Love Foundation in the city of Tunja during the year 2022. Methodology: A quantitative approach is applied through a Quasi-experimental Design, in addition to a program of 16 sessions of Colombian folk dance on the coordinative capacity of rhythm to 12 people with Down syndrome from the Champions of Love Foundation of the city of Tunja, evaluated through the test by Mira Stamback. Results: As shown in the table in the pre and posttest that was applied and after the application of the Colombian folk dance program of 16 sessions, the population had an improvement of 44% in the coordinative capacity of the rhythm. Conclusion: the above shows that the program had a positive effect on the 12 people with Down syndrome from the Champions of Love Foundation in the city of Tunja.
Keywords: Rhythm; Folk Dance; Down Syndrome